1997
DOI: 10.1046/j.1472-765x.1997.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of amylase by the intestinal microflora in cultured freshwater fish

Abstract: The amylase‐producing ability of the intestinal microflora in cultured specimens of ayu, carp, channel catfish, Japanese eel and tilapia was determined. Mean viable counts of aerobes and anaerobes ranged from 1·1×106 to 3·7×108 cfu g−1 and from 1·3×103 to 1·6×108 cfu g−1, respectively. Aeromonas spp. and Bacteroidaceae were predominant in four to five fish species. Of 206 strains examined, 65 (31·6%) produced ≥0·01 U amylase ml−1. The percentage of producers differed among families and genera of bacteria and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 2 publications
1
85
2
Order By: Relevance
“…This is because the gut microflora in fishes and crustaceans can metabolize several nutrients that the host cannot and can convert them to end products that are beneficial to the host (Suzer et al, 2007;Hoyoux et al, 2009). It has been reported that intestinal microorganisms have a beneficial effect on the digestive process of fish such as in the microbial breakdown of cellulose (Saha and Ray, 1998;Bairagi et al, 2002;Saha et al, 2006;Mondal et al, 2008;Ray et al, 2010), starch (Sugita et al, 1997), protein (Chong et al, 2002;Fu et al, 2005;Silvia et al, 2006) and lipid (Tanu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This is because the gut microflora in fishes and crustaceans can metabolize several nutrients that the host cannot and can convert them to end products that are beneficial to the host (Suzer et al, 2007;Hoyoux et al, 2009). It has been reported that intestinal microorganisms have a beneficial effect on the digestive process of fish such as in the microbial breakdown of cellulose (Saha and Ray, 1998;Bairagi et al, 2002;Saha et al, 2006;Mondal et al, 2008;Ray et al, 2010), starch (Sugita et al, 1997), protein (Chong et al, 2002;Fu et al, 2005;Silvia et al, 2006) and lipid (Tanu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Archea, which are normally prolific in Rhopaloides odorabile sponges, were not detected after exposure to Cu 2+ concentration of 19.4 µg l -¹ for 14 days. It is well known that fish harbour the communities of microorganisms in the intestinal tract that also fulfill necessary functions (Sugita et al 1997(Sugita et al , 2002. Correspondingly, xenobiotics that inhibit bacterial abundance and qualitative composition in the intestinal tract of fish larvae, as well as their activities, will have negative effects on food assimilation efficiency and antibacterial abilities against fish pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…Several investigators have reported the presence of enzyme producing bacteria in the digestive tract of Oreochromis spp. (Sugita et al, 1997;Bairagi et al, 2002;Saha et al, 2006;Ray et al, 2007;Mondal et al, 2008;Sarkar and Ghosh, 2014;Sasmal and Ray, 2015). The present study is the first one demonstrating adherent bacteria and yeasts on the gut surfaces of Oreochromis niloticus along with antagonistic properties against the potential fish pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, GI tract of the Oreochromis spp. have been evaluated in several studies in course of enumerating extracellular enzyme-producing (Sugita et al, 1997;Bairagi et al, 2002;Saha et al, 2006;Ray et al 2007;Sarkar and Ghosh, 2014;Sasmal and Ray, 2015), or pathogenic bacteria (Plumb, 1997;Son et al, 1997;Marathe et al, 2016). Enzymatic potential of gut bacteria isolated from various fish species have been displayed as the likely function that probiotics might accomplish.…”
mentioning
confidence: 99%